Antioxidant Activity of Bioactive Peptides on Protein Hydrolyze of Bombay Duck (Harpodon nehereus) from Papain Hydrolysis - Rahman, R. Fathul; Buchari, Dewita; Hasan, Bustari (Fakultas Perikanan dan Kelautan Universitas Riau, 2023)
This study aimed to examine the antioxidant activity of bioactive peptides on protein hydrolyzes of Bombay duck (Harpodon nehereus)from hydrolysis using papain enzyme. This research used an experimental method, with a wholly randomized non-factorial design consisting of enzyme concentration factors (1,5, 2, and 2,5%). Parameters tested include chemical composition tests of Bombay duck's meat, flour, and protein hydrolyze, identification of short peptide chains, and antioxidant activity. The results showed that Bombay duck protein hydrolyzes with papain enzyme concentration. There was a significant difference, where the enzyme concentration of 2,5% has the highest degree of hydrolysis of 69,18%. The chemical composition of meat was water 73.15% (ww), protein 81.97% (dw), ash 5.57% (dw), and fat 4,49% (dw). The chemical composition of flour Bombay duck was water 8.32% (ww), protein 79.88% (dw), ash 4,89% (dw), and fat 3,41% (dw). The best treatment of Bombay duck protein hydrolyze at an enzyme concentration of 2.5% resulted in a chemical composition of water 6.73% (ww), protein 80,56 % (dw), ash 5,53 % (dw) and fat 3,11 % (dw). The results of the identification of peptide compounds were L-Pro-L-Ile, L-Leu-L-pro, L-Arg-D-Pro, Leu-Ala-Arg-Leu, and L-Thr-L-pro-L-lys. Furthermore, DPPH free radicals (IC50) scavenging power was 5.19%.